Assess Severity of Organophosphate Poisoning by Peradeniya Organophosphorus Poisoning (Pop) Scale - Brinda Mevada; Sangita Parikh; Kaushika Chaudhari; Zalak Gadani; Leena Dabhi; Vikas Nayi; Rohit Zarivala (Institute of Medico-legal Publications Pvt Ltd, 2022)
Background: OP compound poisoning is an important indication for emergency admission in most hospitalsthroughout India. WHO estimates that approximately 3 million pesticide poisoning occur worldwide and causingmore than 2,20,000 deaths. Peradeniya Organophosphorus poisoning scale grades the severity of OP poisoningand assess the prognosis of patients. The present study aims to correlate serum cholinesterase level and theclinical criteria score described by the POP scale at initial presentation and the severity of poisoning with need forventilation and outcome.Methods: A hospital based cross sectional observational study was conducted over period from october 2017to october 2019 at tertiary care hospital, Ahmedabad. Total of 75 patients were evaluated for POP scale andserum cholinesterase levels for assessment of severity of poisoning. POP scale was studied to predict the need forventilatory support, duration of hospital stay and outcome.Conclusion: In our study males were most commonly involved (61%). Most commonly affected age group wasbetween 25 to 40 years. 72% had mild, 25.33% had moderate, 2.77% had severe op poisoning according to POPscore. Respiratory failure was more common in moderate and severe op poisoning, 68.42% and 100% respectively.Prolonged icu stay(more than 5 days) was required in moderate and severe group of op posisoning, 63% and 50%respectively as compared to mild group(16.67%). 100% mortality was noted in severe group, 47.36% was noted inmoderate group.